2013
DOI: 10.1007/s00436-013-3414-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, sequencing, and biological characterization of GRA4 gene of Toxoplasma gondii

Abstract: In the present study, GRA4 (dense granule antigen) gene of Toxoplasma gondii was cloned, sequenced, and biologically characterized. The nucleotide sequence data obtained were analyzed and submitted in GenBank database (accession no. EU660037). Analysis of nucleotide sequence of GRA4 gene revealed 99.2 % homology with the published sequence (accession no. M76432). The gene segment (open reading frame) of 1,054 bp was further amplified and re-cloned in expression vector pET-32a. The recombinant protein obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Electrophoresis of GRA-4 recombinant protein using SDS PAGE (Figure -5) showed the protein recombinant with molecular weight of 48 kDa. This Available at www.veterinaryworld.org/Vol.13/October-2020/6.pdf data differed from data observed by Ram et al [23] and Meng et al [24]. The difference in molecular weight is related to the histidine-tagged application [18].…”
Section: T Gondii=toxoplasma Gondiimentioning
confidence: 78%
“…Electrophoresis of GRA-4 recombinant protein using SDS PAGE (Figure -5) showed the protein recombinant with molecular weight of 48 kDa. This Available at www.veterinaryworld.org/Vol.13/October-2020/6.pdf data differed from data observed by Ram et al [23] and Meng et al [24]. The difference in molecular weight is related to the histidine-tagged application [18].…”
Section: T Gondii=toxoplasma Gondiimentioning
confidence: 78%
“…The GRA proteins, which are highly expressed by the parasite, constitute the circulating antigens in the acute and chronic phases of infection and are of primary relevance to host immunity. Studies demonstrated the ability of several GRA antigens to confer protective immunity in mice infected with T. gondii [ 32 , 33 ], in particular GRA4 [ 17 , 34 - 38 ]. Reports demonstrated that GRA4 might be used to design novel and alternative diagnostic methods for toxoplasmosis [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The GRA proteins, which are highly expressed by the parasite, constitute the circulating antigens in the acute and chronic phases of infection and are of primary relevance to host immunity. Studies demonstrated the ability of several GRA antigens to confer protective immunity in mice infected with T. gondii [32,33], in particular GRA4 [17,[34][35][36][37][38]. Reports demonstrated that GRA4 might be used to design novel and alternative diagnostic methods for toxoplasmosis [39,40].…”
Section: Introductionmentioning
confidence: 99%